A long-term evaluation of wind energy resources in Republic of Moldova. (September 2021) - Stavarache, Gheorghe; Ciortan, Sorin; Rusu, Eugen
Abstract: The paper presents an analysis of the wind energy availability on long-term basis in the Republic of Moldova. This is motivated by the necessity of increasing the renewable energy sources in the global energy portfolio of the Republic of Moldova. Although there are some studies on this subject, concluding that there is a satisfactory wind energy potential, there are no references on the future evolution of the wind energy. Starting from the analysis of the historical wind speed data corresponding to the 31-year period 1990–2020 and taking into account the most significant geographic and civil requirements, several locations were chosen as possible targets for the future wind farms placement. An analysis of the predicted wind data for the 31-year period 2020–2050 based on RCP4.5 scenario, allowed to identify the optimal areas for the wind energy extraction in the republic of Moldova.